The Antarctic ozone hole during 2013 - Andrew Klekociuk; Krummel, PB; Tully, MB; Gies, HP; Simon Alexander; Fraser, PJ; Henderson, SI; Javorniczky, J; Shanklin, JD; Schofield, R; Stone, KA (2015)
We review the 2013 Antarctic ozone hole, making use of various ground-based, in-situ and remotely-sensed ozone measurements, ground-based measurements of ultraviolet radiation and meteorological reanalyses. Based on analysis of 34 years of satellite records spanning 1979-2013 (which excludes 1995), we find that in terms of maximum area, minimum ozone level and total ozone deficit, the ozone hole in 2013 was typical of other years of moderate ozone loss. The estimated integrated ozone mass effectively depleted within the ozone hole of 2013 was approximately 1037 Mt, which was the 17th largest deficit on record and 41% of the peak deficit observed in 2006. Anomalously cold winter temper-atures in the lower stratosphere over Antarctica and concurrent strong and stable vortex conditions favoured the potential for strong ozone depletion in 2013. However, anomalous warming of the polar vortex that occurred from late Au-gust limited the overall severity of ozone depletion during spring, and resulted in the relatively early breakup of the ozone hole in mid-November.